2003
DOI: 10.1109/memb.2003.1266049
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing particle collection for enhanced surface-based biosensors

Abstract: T here exists a number of applications where a method of rapid detection of particlulate biomatter on the micron-and submicron scale, such as cells, bacteria, proteins, and viruses, is of great importance. Such applications include the development of point-of-care diagnostic devices for the detection of rare cells, the testing of water quality for the detection of microorganisms , and the monitoring of the environment for the detection of bioweapons such as anthrax. In order to detect such particles, a highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 26 publications
3
38
0
Order By: Relevance
“…This suggested that the electric field acts directly on the particles hence DEP were occurred. This has confirmed the previous works done by Mohtar [3], Hoettges [5] and Hubner [6]. This has also means that the manipulation of colloids is selective according to the electrical potential supplied.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This suggested that the electric field acts directly on the particles hence DEP were occurred. This has confirmed the previous works done by Mohtar [3], Hoettges [5] and Hubner [6]. This has also means that the manipulation of colloids is selective according to the electrical potential supplied.…”
Section: Resultssupporting
confidence: 89%
“…al. [5]. Zipper geometry is selected because the geometry will have electric potentials of opposing polarity applied allowing focusing of particles across a large area toward a central spot.…”
Section: Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Anomalous frequency effects, not explainable by DEP forces alone, were also observed by Voldman et al 67 for particles held in traps, and this was also attributed to electrohydrodynamic flow. Hoettges et al 82 later designed a DEP particle trap to exploit such fluid flow effects in a so-called "zipper" electrode design. A DEP device architecture that offers interesting possibilities for particle transport without the use of fluid flow is the ratchet geometry described by Gonzalez and Remcho.…”
Section: Technologymentioning
confidence: 99%
“…For example, they have been developed as single-cell trapping devices for fluids having conductivities ͑1.25 S/m͒ typical of physiological fluids and culture growth conditions. 86 A zipper electrode design has been described by Hoettges et al 82 in the form of an array of interlocking, approximately circular electrode pads. As already mentioned, this design exploits field-induced electrohydrodynamic fluid flow to direct particles toward the electrode pads, and then DEP forces to trap them.…”
Section: Technologymentioning
confidence: 99%